Chemical composition and potential of use amethyst stone extraction residue as an agricultural fertilizer - Santos, Eliane Pereira dos; Fioreze, Mariele; Benatti, Marco Eliandro (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Ametista do Sul, northem RS, whose main economic activity practice amethyst stone extraction. The mining takes place in the underground system, resulting in tons of solid waste (tailings) which are mostly deposited in the hillsides without any care or discretion. This study aimed to determine the chemical composition of wastes, in order to evaluate the potential use of these as agricultural fertilizer, by incorporation into the soil. Basic determinations were performed according ROLAS, for the parameters pH, organic matter, nitrogen, potassium, phosphorus, calcium and magnesium. Samples were collected in eight different sampling points, taking into account the differences between mining wastes. The results indicated the mineral character of waste, due to low levels of organic matter and nitrogen, and for these two parameters waste is not suitable for fertilization. As for macronutrients P, K, Ca and Mg, the residue has demonstrated good yields, being in high concentration, these being suggested the use as agricultural fertilizer by soil incorporation.